Potensi Oleoresin Gulma Daun Siam (Chromolaena odorata) pada Mortalitas Hama Lalat Buah (Bactrocera cucurbitae) pada Uji in-vitro - Ropalia, Ropalia; Apriyadi, Rion; Yurenza, Nadia (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2023)
Fruit flies are the main pests that attack various types of fruit vegetables and fruits that can caused a damage in the quality and quantity of production. Fruit flies controlling by chemical insecticides is common to use nowadays, but excessive use of chemical insecticides has a negative impact on the health and environment. One alternative to control the fruit flies is using oleoresins of Chromolaena odorata leaf. This study aims to determine the effect of C. Odorata leaf oleoresin on increasing the mortality of fruit fly pests (Bactrocera cucurbitae). This research used an experimental method with Completely Randomized Design (CRD) which had 6 treatment levels, namely: N0 (Aquadest), N1 (Oleoresins 2%), N2 (Oleoresins 4%), N3 (Oleoresins 6%), N4 (Oleoresins 8%), N5 (Oleoresins 10%), was replicated 4 times so there were 24 experimental units. The results showed that the application of C. Odorata leaf oleoresin had no sigificant effect on mortality percentage and mortality rates, but oleoresin had the potential to increasing fruit fly mortality as concentrations increased. It is necessary to test the increasing concentration of oleoresin > 10% to control fruit fly pests.